2022
DOI: 10.1038/s41440-022-00898-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-based mechanism exploration of pulmonary arterial hypertension pathogenesis: novel lessons from explanted human lungs

Abstract: Background: Metabolic pathways have been shown to participate in the pathogenesis of pulmonary arterial hypertension (PAH). We investigated the metabolic pro le shifts to reveal molecular mechanisms underlying PAH.Methods: Explanted human lung tissues from 18 PAH patients were collected. The lung tissues far from the tumor from 16 lung cancer patients were taken as controls. Lung tissues were analyzed by LC-MS/MS based non-target metabolomics method. Pathway analysis was performed with KEGG database and Metabo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The higher the thymine level, the better the patient prognosis. A direct proportion was found between the spermine level and the patients' cardiac function [48].…”
Section: Pah Pathogenesismentioning
confidence: 87%
“…The higher the thymine level, the better the patient prognosis. A direct proportion was found between the spermine level and the patients' cardiac function [48].…”
Section: Pah Pathogenesismentioning
confidence: 87%
“…Ding et al. found that the AKT pathway is inactivated in PASMCs exposed to hypoxia as well as in human and rat pulmonary hypertensive lungs ( 172 ). We hypothesize that in the early stage of PH, the body inhibits the PI3K/AKT signaling pathway to prevent activation of its downstream pathway from aggravating disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled quality control (QC) sample was prepared by mixing equal volumes of each extracted supernatant and injected every 10 samples. The metabolites were separated and detected using Waters 2D UPLC (waters, USA) tandem Q exactive high-resolution mass spectrometer (Thermo Fisher Scientific, USA) [50]. Chromatographic separation was conducted using a BEH C18 column (1.7 µm; 2.1 mm × 100 mm, Waters, Milford, MA, USA).…”
Section: Untargeted Metabolomics Analysismentioning
confidence: 99%